Study on the performance of different uranium isotopic codes used in nuclear safeguards activities. Issue 4 (April 2019) - Darweesh, M.; Shawky, S.
Abstract: Accurate characterization of Nuclear Materials (NMs) for nuclear safeguards purposes requires studying the optimal conditions over a wide range of experimental conditions. Gamma spectroscopy is commonly used to measure the 235 U enrichment in NMs bearing samples. Several commercials Codes such as the Multi Group Analysis (MGA ++ ), the Multi Group Analysis for Uranium (MGAU) and the "Fixed energy, Response function Analysis with Multiple efficiencies" (PC/FRAM) are used to measure 235 U enrichment. Many factors, such as sample enrichment, density, homogeneity, geometry, and container type may affect the results of measurement. This work studies the effect of these factors on the performance of each of the three codes to estimate uranium enrichment. The results are compared to determine the optimum conditions and best performance among the three codes for achieving the most accurate estimation of 235 U enrichment in the measured samples.